2011
DOI: 10.1167/iovs.11-7300
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Inhibition Decreases Diode Laser–Induced Choroidal Neovascularization Development in Rats: P17 and P144 Peptides

Abstract: TGF-β inhibition with these peptides represents a promising new therapeutic line for CNV targeting a different pathway than current therapies. More studies are needed to assess this effect on early CNV, alone or in combination with anti-VEGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
2
24
0
1
Order By: Relevance
“…This may be based on its role in supressing the stalk-cell phenotype in endothelial tip-cells via the modulation of Alk1 and Alk5 mediated TGFB superfamily signalling [26]. In a pathological context, we have previously demonstrated that inhibition of TGFB can reduce CNV lesion size in the laser-induced CNV model [3537]. This confirms that blocking of not only VEGF but also of other targets can be effective in preventing CNV.…”
Section: Discussionmentioning
confidence: 72%
“…This may be based on its role in supressing the stalk-cell phenotype in endothelial tip-cells via the modulation of Alk1 and Alk5 mediated TGFB superfamily signalling [26]. In a pathological context, we have previously demonstrated that inhibition of TGFB can reduce CNV lesion size in the laser-induced CNV model [3537]. This confirms that blocking of not only VEGF but also of other targets can be effective in preventing CNV.…”
Section: Discussionmentioning
confidence: 72%
“…Nagineni et al [30] demonstrated that TGF-β can induce the secretion of VEGF from the retinal pigment epithelium (RPE) and choroidal cells, and play an important role in CNV in AMD. Two weeks after laser-induced CNV in rats, Zarranz-Ventura et al [31] confirmed that inhibition of TGF-β can reduce the progression of CNV lesions, and Recalde et al [32] drew a similar conclusion. Yuan and Neufeld [38] found that whereas microglial cells do not express TGF-β 2 in normal optic nerve heads and rarely contain TGF-β 1 , they can express TGF-β 2 in glaucomatous optic nerve heads, and a few of them contain TGF-β 1 .…”
Section: Discussionmentioning
confidence: 88%
“…Apart from VEGF, other pro-angiogenic factors like PDGF-β [17,24,25] , FGF [26][27][28][29] , TGF-β [17,[29][30][31][32] , and IL-8 [33][34][35][36] were also reported to be involved in the pathological process of AMD. Zehetner et al [24] compared the plasma levels of PDGF-β in neovascular AMD patients with healthy controls and found that there was a significantly higher plasma PDGF-β level in neovascular AMD patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…A synergistic association with b-FGF and tumor necrosis factor-alpha (TNF-α) over VEGF transcription has been reported, suggesting that TGF-β may work in concert with other cytokines in VEGF upregulation [19]. These findings led us to speculate that selective blockade of TGF-β would abate CNV development, a hypothesis recently confirmed in a study performed with two anti-TGF-β inhibitor peptides in a laser induced CNV model [20]. In this study, we evaluated the effect of these peptides on CNV induction, with treatments administered 48 hours after laser application.…”
Section: Introductionmentioning
confidence: 82%